Laser and electron-beam powder-bed additive manufacturing of metallic implants: A review on processes, materials and designs - Sing, Swee Leong (2018)
Additive manufacturing (AM), also commonly known as 3D printing, allows the direct fabrication of functional parts with complex shapes from digital models. In this review, the current progress of two AM processes suitable for metallic orthopaedic implant applications, namely selective laser melting (SLM) and electron beam melting (EBM) are presented. Several critical design factors such as the need for data acquisition for patient-specific design, design dependent porosity for osteo-inductive implants, surface topology of the implants and design for reduction of stress-shielding in implants are discussed. Additive manufactured biomaterials such as 316L stainless steel, titanium-6aluminium-4vanadium (Ti6Al4V) and cobalt-chromium (CoCr) are highlighted. Limitations and future potential of such technologies are also explored.